Cohomological and Geometric Approaches to Rationality Problems New Perspectives - Bogomolov, Fedor; Tschinkel, Yuri (Progress in Mathematics, 2010)
Rationality problems link algebra to geometry. The difficulties involved depend on the transcendence degree over the ground field, or geometrically, on the dimension of the variety. A major success in 19th century algebraic geometry was a complete solution of the rationality problem in dimensions one and two over algebraically closed ground fields of characteristic zero. These advances have led to many interdisciplinary applications of algebraic geometry. This comprehensive text consists of surveys and research papers by leading specialists in the field. Topics discussed include the rationality of quotient spaces, cohomological invariants of finite groups of Lie type, rationality of moduli spaces of curves, and rational points on algebraic varieties. This volume is intended for research mathematicians and graduate students interested in algebraic geometry, and specifically in rationality problems. I. Bauer C. Böhning F. Bogomolov F. Catanese I. Cheltsov N. Hoffmann S.-J. Hu M.-C. Kang L. Katzarkov B. Kunyavskii A. Kuznetsov J. Park T. Petrov Yu. G. Prokhorov A.V. Pukhlikov Yu. Tschinkel.